N6-Methylandenosine-Related lncRNAs in Tumor Microenvironment Are Potential Prognostic Biomarkers in Colon Cancer - Zhang, Hongliang; Zhao, Lei; Li, Songyan; Wang, Jing; Feng, Cong; Li, Tanshi; Du, Xiaohui (Frontiers in Oncology, 2021)
Background: LncRNA dysregulation and the tumor microenvironment (TME) have been shown to play a key role in the progression and prognosis of colon cancer (CC). Our aim is to reveal the potential molecular mechanism from the perspective of lncRNA in the TME and provide the candidate biomarkers for CC prognosis. Methods: ESTIMATE analysis was used to divide the CC patients into high and low immune or stromal score groups. The expression array of lncRNA was re-annotated by Seqmap. Microenvironment associated lncRNAs were filtered through differential analysis. The m6A-associated lncRNAs were filtered by pearson correlation analysis. Lasso cox regression analysis were performed to construct the m6A- and tumor microenvironment- related lncRNA prognostic model (m6A-TME-LM). Kaplan Meier analysis was used to assess the prognostic efficacy of candidate lncRNAs. The candidate genes’ functions were annotated by enrichment analyses. Results: We obtained 25 common differentially expressed lncRNAs (DELs) associated with immune microenvironment and m6A related genes for subsequent lasso analysis. Four out of these DELs were selected for the m6A-TME-LM. All the four lncRNAs were related to overall survival and a test set testified the result. Further stratification analysis of the m6A-TME-LM retained its ability to predict OS for male and chemotherapy adjuvant patients and performed an excellent prognostic efficacy in the TNM stage III and IV subgroups. Network analysis also found the four lncRNAs mediated co-expression network were associated with tumor development. Conclusion: We constructed a m6A-TME-LM which could provide better prognostic prediction of CC.